Between a Rocket and a Hard Place: Military Space Technology and Stability in International Relations. Issue 1 (2nd January 2017) - Sariak, George
ABSTRACT: Military space technology is both stabilizing and destabilizing in international relations in respect to the distinction between passive and active applications. Space has been militarized from the dawn of humanity's entry to space, but it is presently not weaponized. Although the benefits of passive military space technology are vast and promising, access to these benefits is exclusive and dominated by certain actors, leading other states to possible destabilizing influences of insecurity. Also, the failures of space law and treaties in regulating active military space technology stand to undermine the stabilizing effects of passive military space technology if not addressed.